Implementasi Kebijakan Melalui Model MSN Approach pada Pengelolaan Sampah di Kabupaten Bengkalis - Siti Zaleha Kurnia Putri; Dadang Mashur (Journal of Education Technology Information Social Sciences and Health, 2025)
This research is motivated by the ongoing waste management issues faced by local governments. One of the regions experiencing this problem is Mandau District, which produces 30,131.40 tons of waste annually. The waste generated by the community is disposed of at the Final Processing Site (TPA) located on Rangau Street, Bathin Solapan District. This study aims to analyze the Policy Implementation Model through the MSN Approach in waste management carried out by the Technical Implementation Unit for Waste Management in Mandau and Bathin Solapan Districts, Bengkalis Regency. The research uses a qualitative method with data collected through in-depth interviews with UPTD Waste Management officers, observation, and documentation. This study applies the Implementation Theory by Kadji (2015), which includes three main indicators: the Mentality Approach, System Approach, and Networking Approach. The findings reveal that the implementation of waste management policies in Bengkalis Regency has not yet been optimal. The mentality approach is hindered by low public awareness and participation, the system approach requires more structured planning and coordination, while the networking approach demands strong collaboration between the government, community, and private sector. The main obstacles include low staff motivation, lack of public participation, limited facilities, unstructured implementation strategies, and budget constraints. Capacity building and synergy among stakeholders are needed to overcome these challenges.